1996
DOI: 10.1002/(sici)1099-0992(199601)26:1<75::aid-ejsp738>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

The impact of differentially valued overlapping categorizations upon the differentiation between positively, negatively, and neutrally evaluated social groups

Abstract: The present study attempted to determine whether the impact of overlapping categorizations upon intergroup differentiation should be attributed to cognitive category differentiation processes or whether motivational social identity processes do also intervene. Experimentally created groups were placed in one of four overlapping categorization conditions: the overlapping category was either absent or it was affectively positive, negative, or neutral. These groups were also differentially evaluated by providing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…One possible explanation for the latter result is that there is an inherent complexity involved with making categorizations on the basis of two varying criteria (see Brown & Turner, 1979;Hogg & Abrams, 1988;Messick & Mackie, 1989;Vanbeselaere, 1996;Wilder, 1986). In response to this complexity, people may revert to an interpersonal orientation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One possible explanation for the latter result is that there is an inherent complexity involved with making categorizations on the basis of two varying criteria (see Brown & Turner, 1979;Hogg & Abrams, 1988;Messick & Mackie, 1989;Vanbeselaere, 1996;Wilder, 1986). In response to this complexity, people may revert to an interpersonal orientation.…”
Section: Discussionmentioning
confidence: 99%
“…In his conceptualization of the differentiation process, Doise (1978) argues that when two categorizations are crossed, the accentuation of perceived differences between the categories on one dimension will be weakened by a countervailing accentuation of perceived similarities on the shared category dimension. Consistent with this, it has been found that when members of different groups are made aware of shared membership on a second social category, levels of bias are either reduced (Hewstone, Islam, & Judd, 1993;Vanbeselaere, 1991Vanbeselaere, , 1996 or eliminated (Deschamps & Doise, 1978;Diehl, 1990;Vanbeselaere, 1987). 1 The simultaneous activation of superordinate and subordinate categories can be viewed as a special sort of crossed categorization, with the shared category at a more inclusive level of the category hierarchy.…”
mentioning
confidence: 99%
“…Deschamps and Doise (1978) suggested that by simultaneously combining two cross-cutting dimensions of social categorization, opposing accentuation and assimilation principles would effectively cancel each other out and reduce intergroup bias. This approach of combining two crosscutting categorizations has met with mixed success in terms of reducing intergroup bias (Brown & Turner, 1979;Crisp, Hewstone, & Rubin, 2001;Deschamps & Doise, 1978;Vanbeselaere, 1987Vanbeselaere, , 1996. The majority of studies produce a pattern of evaluation where any group associated with the ingroup is evaluated positively to some extent but where negative evaluations are still directed toward those people who are in the outgroup according to both categorical criteria (Diehl, 1990;Ensari & Miller, 1998;Hewstone, Islam, & Judd, 1993;Kenworthy, Canales, Weaver, & Miller, 2003;MarcusNewhall, Miller, Holtz, & Brewer, 1993;Urada & Miller, 2000;Vanbeselaere, 1987;see Crisp & Hewstone, 1999;Urban & Miller, 1998, for reviews).…”
Section: Multiple Social Categorizationmentioning
confidence: 99%
“…They proposed that in-group bias is simply exhibited in order to assign meaning to the uncertain situation of being categorized as a group member (Lemeyre and Smith, 1985). Despite the fact that cognitive activities, which are involved in the process of categorization (Turner et al, 1987), are of great importance, people's motivations cannot be overlooked in the study of intergroup relations (see also Vanbeselaere, 1996).…”
Section: Discussionmentioning
confidence: 54%